ADRF Network Hosts Research Conference to Advance Uses of Administrative Data in the United States - King, Monica M (International Journal of Population Data Science, 2021)
The Administrative Data Research Facilities (ADRF) Network is a new U.S.-based effort aimed at advancing the uses of administrative data in social science research. Together with Georgetown University’s Massive Data Institute, the ADRF Network hosted its first conference in November 2017 to share approaches and build collaborative opportunities. The conference illustrated the importance of private sector data, the need for data intermediaries, and the essential process of building trust in moving forward this emerging field in the United States.